Rapid Crown Root Development Confers Tolerance to Zinc Deficiency in Rice - Nanda, Amrit K.; Wissuwa, Matthias (Frontiers in Plant Science, 2016)
Zinc (Zn) deficiency is one of the leading nutrient disorders in rice (Oryza sativa). Many studies have identified Zn efficient rice genotypes, but causal mechanisms for Zn deficiency tolerance remain poorly understood. Here we report a detailed study of the impact of Zn deficiency on crown root development of rice genotypes, differing in their tolerance to this stress. Zn deficiency delayed crown root development and plant biomass accumulation in both Zn efficient and inefficient genotypes, with the effects being much stronger in the latter. Zn efficient genotypes had developed new crown roots as early as three days after transplanting (DAT) to a Zn deficient field and that was followed by a significant increase in total biomass by 7 DAT. Zn-inefficient genotypes developed few new crown roots and did not increase biomass during the first seven days following transplanting. This correlated with Zn efficient genotypes retranslocating a higher proportion of shoot Zn to their roots, compared to Zn inefficient genotypes. These latter genotypes were furthermore not efficient in utilizing the limited Zn for root development. Histological analyses indicated no anomalies in crown tissue of Zn-efficient or inefficient genotypes that would have suggested crown root emergence was impeded. We therefore conclude that the rate of crown root initiation was differentially affected by Zn deficiency between genotypes. Rapid crown root development, following transplanting, was identified as a main causative trait for tolerance to Zn deficiency and better Zn retranslocation from shoot to root was a key attribute of Zn-efficient genotypes.